Metabolite profiling reveals organ‐specific flavone accumulation in Scutellaria and identifies a scutellarin isomer isoscutellarein 8‐O‐β‐glucuronopyranoside. (20th December 2021) - Askey, Bryce C.; Liu, Dake; Rubin, Garret M.; Kunik, Andrew R.; Song, Yeong Hun; Ding, Yousong; Kim, Jeongim
Abstract: Scutellaria is a genus of plants containing multiple species with well‐documented medicinal effects. S. baicalensis and S. barbata are among the best‐studied Scutellaria species, and previous works have established flavones to be the primary source of their bioactivity. Recent genomic and biochemical studies with S. baicalensis and S. barbata have advanced our understanding of flavone biosynthesis in Scutellaria . However, as over several hundreds of Scutellaria species occur throughout the world, flavone biosynthesis in most species remains poorly understood. In this study, we analyzed organ‐specific flavone profiles of seven Scutellaria species, including S. baicalensis, S. barbata, and two species native to the Americas ( S. wrightii to Texas and S. racemosa to Central and South America). We found that the roots of almost all these species produce only 4′‐deoxyflavones, while 4′‐hydroxyflavones are accumulated exclusively in their aerial parts. On the other hand, S. racemosa and S. wrightii also accumulated high levels of 4′‐deoxyflavones in their aerial parts, different with the flavone profiles of S. baicalensis and S. barbata . Furthermore, our metabolomics and NMR study identified the accumulation of isoscutellarein 8‐ O ‐β‐glucuronopyranoside, a rare 4′‐hydroxyflavone, in the stems and leaves of several Scutellaria species including S. baicalensis and S. barbata, but not in S. racemosa and S. wrightii . Distinctive organ‐specific metabolite profiles among Scutellaria species indicate the selectivity and diverse physiological roles of flavones.